Gasoline Direct Injection - Three dimensional CFD study employing fluent V 4.25 / Sharum Md. Jilis - Md. Jilis, Sharum (2002)
After more than 15 years of research, the Mitsubishi GDI engine is a historic breakthrough. The new 4G93 GDI engine combines the outstanding performance of a petrol engine with the fuel economy of a diesel, while significantly reducing CO₂ emissions. In conventional engines, fuel and air are mixed outside the cylinder. This ensures waste between the mixing point and the cylinder, as well as imperfect injection timing. But in the Mitsubishi GDI engine, petrol is injected directly into the cylinder with precise timing, eliminating waste and inefficiency. My project title is Gasoline Direct Injection - Three Dimensional CFD Study Employing Fluent V 4.25. Features tested variation of flow and efficiency of combustion The gasolines direct injections are new technologies in fuelling consumption. In order to justify the truth or the myth of the GDI engine, a simulation had been conducted. Changing the geometry of the valves hopefully can create a better view in the improvement of the modem technologies in engine combustion. Similarly, the Z-wall (piston head) displacement was the moving plane with speed 13.91 m/s and 27.81 m/s. The temperature of the Z-wall is 423K and the W-wall 393K. The flow was model as turbulence and swirl. Relevant file names Command files, Log files, Geometry files, Grid files, Case files and Data files.